Análisis de contenidos del uso del lenguaje inclusivo de género en los medios impresos de Riobamba período octubre 2019- marzo 2020 - María Fernanda, Castro Duque (2021)
ABSTRACT The main objective of this research is the content analysis on the use of gender-inclusive language in the print media of Riobamba, period October 2019 to March 2020. To support the study, the development of the theoretical framework was strengthened, same as It is made up of definitions such as: communication, communication theories, theory allied to the functionalist study, gender, inclusive language and masculine generic. The methodology that was applied was the qualitative and quantitative method, due to the requirement of wanting to determine the influence of the use of the generic masculine, inclusive or exclusive content and sexism focused on the linguistic aspect, four interviews were also carried out, two of editors of the different print media and two experts in content writing and social communicator. The interviewees coincide when mentioning that the print media are constantly learning to improve gender-inclusive practices in the content from the parameters established by the Royal Spanish Academy (RAE), with respect to the interviewees they agree that the print media are free to apply inclusive language, as long as it is a policy established by the media, since there are no laws in relation to language that prohibit it. Finally, to obtain accurate results, a content analysis table was used to study in depth and obtain a logical answer for our proposed objectives, and thus propose the development of a scientific article on the subject investigated and send it to the scientific Chasqui journal. Keywords: inclusive language, communication, print media, linguistic sexism. Reviewed by: Danilo Yèpez Oviedo English professor UNACH 060157469